Does introduction to the school field affect interest in becoming an economics teacher? - Sholeh, Badrus; Rusmaini, Rusmaini; Holisoh, Ade (Universitas Riau Kepulauan, 2025)
The purpose of the school field introduction (PLP) is to train skilled educators. PLP activities are designed to increase interest in education and knowledge about the teaching profession, even though not all students want to become teachers. The purpose of this study is to determine how school field introduction affects the enthusiasm of seventh-semester Economics Education students at Pamulang University in teaching economics. This study uses quantitative and associative research methodologies. The research sample consisted of one hundred students who had participated in the PLP. Data were collected through observation and questionnaires. The research instruments were tested for validity and reliability. Simple linear regression was used to analyse the data. According to the research findings, the desire of Pamulang University Economics Education Bachelor’s degree students to become economics teachers is influenced by their field introduction. The inclusion of the school field had an impact on interest in becoming an economics teacher, as indicated by the estimated t value > t table (9.189 > 1.984) and significance < 0.05 (0.000 < 0.05), after which Ho was discarded.